Comparison of Porosity in Thermoplastic Filling Using MTA with Ca(OH)2 and MTA with Nano Chitosan by using Scanning Electron Microscope (SEM) - Wedagama, Dewa Made (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Porosity often occurs after root canal treatment. Various sealers are used to close all the gaps between the root canal system and the outer surface of the tooth. The currently used root canal sealers include MTA, Ca(OH)₂, and nano chitosan (NC). The purpose of this study was to determine the difference in porosity levels of root canals treated with MTA sealer combined with Ca(OH)₂ versus MTA sealer combined with NC. Method: This study used 16 human adult incisor samples (tooth #11), divided into two groups. The first group received MTA sealer with Ca(OH)₂, and the second group received MTA sealer with NC, both applied using the thermoplastic filling technique. After treatment, the samples were examined using scanning electron microscopy (SEM) to measure porosity. Results: The porosity measurements (in micrometers, μm) for the first group (MTA with Ca(OH)₂) were: 12.24, 7.98, 9.81, 8.19, 10.85, 7.87, 8.43, and 8.96. The second group (MTA with NC) showed porosity values of: 7.73, 2.48, 6.80, 3.85, 1.32, 4.66, 3.98, and 4.22. The mean porosity in the first group was 9.29 μm, while in the second group it was 4.38 μm. Conclusion: Statistical analysis showed a t-value of 5.31 with p < 0.001, indicating a significant difference between the two groups (p < 0.05). This suggests that MTA sealer combined with nano chitosan results in significantly lower porosity and better root canal filling density compared to MTA sealer combined with Ca(OH)₂.